Maharatul Kalam Learning Strategy At MA Darul Lughoh Wal Karomah Kraksan: استراتيجيات تعليم مهارة الكلام في المدرسة الثانوية الإسلامية دار اللغة والكرامة كركسأن - Syakdiyah, Halimatus; Ahmad Zainullah; Yeniati Ulfah (Rayah Al-Islam, 2025)
This research aims to describe and analyze the teaching strategies for speaking skills applied at the Islamic senior high school MA Darul Lughoh Wal Karomah Kraksan. Speaking is a fundamental skill in learning Arabic, especially in Islamic educational environments. The study used a qualitative case study approach, with data collected through observations, interviews, and document analysis. The findings show that teachers employ various active strategies, such as the communicative approach, role-playing, group discussions, oral presentations, and the use of digital media. These strategies have contributed to increasing students’ self-confidence, expanding their vocabulary, and encouraging the use of Arabic in classroom interactions. Among the challenges identified are the lack of Arabic-speaking environments outside the classroom, students' shyness, and limited diversity in teaching methods. The school has addressed these issues by mandating the use of Arabic in daily activities and providing teacher training programs. The study concludes that the speaking skill teaching strategies used at the school are effective and suitable for implementation in religious-based educational institutions.